Good governance and public debate - Giza-Poleszczuk, Anna (Journal of Public Governance, 2007)
Common knowledge and consensus oriented public debate are the key conditions of „good governance”. Common knowledge concerns not only the access to information and facts – due to which social actors are able to articulate rational evaluations, postulates and claims toward public authorities. What is key to common knowledge is the shared knowledge about “society” – opinions, orientations and beliefs of other people, public opinion shape and emotional climate or the features of “our” society as a whole. Both form the basis for the coordination of the social action. The features of the public discourse in Poland turn selfawareness of the social actors in Poland into a trap. The negative image of “society” – presented in the public sphere as passive, low in social capital, traditional etc., and on the other side – “public authorities” as corrupted, cynical and incompetent block the possibility of the dialogue between the two.